2020
DOI: 10.5089/9781513525846.001
|View full text |Cite
|
Sign up to set email alerts
|

The (Subjective) Well-Being Cost of Fiscal Policy Shocks

Abstract: Do discretionary spending cuts and tax increases hurt social well-being? To answer this question, we combine subjective well-being data covering over half a million of individuals across 13 European countries, with macroeconomic data on fiscal consolidations. We find that fiscal consolidations reduce individual well-being in the short run, especially when they are based on spending cuts. In addition, we show that accompanying monetary and exchange rate policies (disinflation, depreciations and the liberalizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 31 publications
(95 reference statements)
1
9
0
Order By: Relevance
“…This refers to an increase in happiness by 1%, a decrease in the ratio of nondistortionary taxes to GDP by 13%. This finding is consistent with the results of Grimes et al (2016) and Eklou and Fall (2020) who mentioned that nondistortionary taxes have a negative impact on happiness. Moreover, GMM model results are also consistent with the finding of Ram (2009) that is the nonexistence of evidence in supporting the hypothesis, including the relationship between public expenditures and happiness.…”
Section: Countries Of the Mena Regionsupporting
confidence: 93%
See 1 more Smart Citation
“…This refers to an increase in happiness by 1%, a decrease in the ratio of nondistortionary taxes to GDP by 13%. This finding is consistent with the results of Grimes et al (2016) and Eklou and Fall (2020) who mentioned that nondistortionary taxes have a negative impact on happiness. Moreover, GMM model results are also consistent with the finding of Ram (2009) that is the nonexistence of evidence in supporting the hypothesis, including the relationship between public expenditures and happiness.…”
Section: Countries Of the Mena Regionsupporting
confidence: 93%
“…They also found that unproductive public spending was associated with higher welfare for middle-class compared to others and transferring part of the spending to the subnational government was linked to higher subjective well-being, but that tax collection through the subnational government was associated with low subjective well-being. As for Eklou and Fall (2020), they investigate the effect of fiscal consolidations on the cost of welfare is by identifying the effect of discretionary spending cuts and tax increases on social welfare. The study covers 13 European countries, including more than half a million individuals during the period from 1980 to 2007.…”
Section: Repsmentioning
confidence: 99%
“…Recent literature has reported the ambiguous effect of trade openness on tax revenue (Cagé & Gadenne, 2018), and India's decision to pull out from the Regional Comprehensive Economic Partnership (RCEP) is aptly appropriate (Deb, 2020). Moreover, fiscal consolidation is likely to adversely impact citizens' well-being, mainly when austerity measures are being applied (Eklou & Fall, 2020).…”
Section: Related Literaturementioning
confidence: 99%
“…To the extent that an individual's performance at work depends on their well-being and their perception of inequality, fiscal consolidation that affects these variables will have an impact on their productivity. Recent research by Eklou et al (2020) revealed a negative relationship between austerity measures and subjective wellbeing. Implications of fiscal consolidation for inequality have also been studied by Wolff and Zacharias (2007) and Agnello and Sousa (2014).…”
Section: Introductionmentioning
confidence: 99%